181 Sleep health concordance among socioeconomically disadvantaged caregiver-child dyads. (3rd May 2021) - Covington, Lauren; Brewer, Benjamin; Blair, Rachel; Hoopes, Elissa; Laurenceau, Jean-Philippe; Patterson, Freda
Abstract: Introduction: Child and caregiver sleep typically occurs within a family system. Disadvantaged families experience disproportionately poorer sleep health than more advantaged families. The extent to which objectively measured sleep health metrics (e.g. duration, timing, regularity, efficiency) are concordant within disadvantaged family systems, such as caregiver-child dyads, is not clear. To address this gap, this study aimed to: (1) characterize sleep health metrics, and (2) identify levels of sleep health concordance among disadvantaged caregiver-child dyads. Methods: 23 disadvantaged dyads were recruited from Philadelphia and Delaware communities. Dyads were eligible if the child was between 6-14 years, slept in the same house as the caregiver at least four nights/week, had no diagnosis of a sleep disorder or use of sleep medication, and qualified for federally funded food assistance programs (e.g., food stamps, WIC or SNAP benefits). Sleep health of the dyads was objectively measured for 7-14 days. Sleep metrics used to characterize the sample were: nighttime sleep duration (hours), time-to-bed, sleep regularity (standard deviation of sleep duration), sleep midpoint (halfway point between sleep onset and wake time) and efficiency (percentage of time spent asleep versus awake). Concordance in sleep health metrics within dyads was calculated using Pearson's correlation coefficients of the average sleep metrics over the monitoring period. Results: Children (46.2% female) slept, on average, 7.96 hours per night, with 1.25 hours of nightly sleep variability, bedtime of 10:47 PM, sleep midpoint of 2:56 AM, and sleep efficiency of 83.55%. Caregivers (mean age = 40.5 years, 85.0% female) slept, on average, 6.92 hours per night, with 1.22 hours of nightly sleep variability, bedtime of 11:24 PM, sleep midpoint of 3:04 AM, and sleep efficiency of 76.29%. Bedtime (r = 0.19, p < 0.001), sleep midpoint (r = 0.39, p < 0.001), and sleep efficiency (r = 0.24, p < 0.001) were significantly concordant among caregiver-child dyads. Conclusion: Given their level of concordance, bedtime, sleep midpoint and efficiency are modifiable factors of sleep health in disadvantaged dyads that could be targeted using family versus individual level interventions. Support (if any): University of Delaware General University Research Grant and School of Nursing SEED funding.